2015
DOI: 10.1177/0885328215596324
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus-eluting dextran and polyglutamic acid hybrid coatings on AZ31 for stent applications

Abstract: Magnesium (Mg)-based cardiovascular stents are promising candidate as the next generation of novel stents. Clinical studies have revealed encouraging outcomes, but late restenosis and thrombogenesis still largely exist. Blood and vascular biocompatible coatings with drug-eluting features could be the solution to such problems. Objective This study was to investigate the feasibility of a three-layer hybrid coating on Mg alloy AZ31 with sirolimus-eluting feature for cardiovascular stent application. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…However, the main drawbacks of conventional Mg alloys are insufficient mechanical strength and rapid corrosion accompanied with hydrogen gas evolution, pH increase, and premature loss of mechanical integrity 5 . Previous studies on surface treatment 6 and element alloying 7 of Mg for stent application showed that these two methods enhanced the performance of Mg and its alloys at some degree but not sufficiently. More sophisticated efforts are in need to fully overcome such weaknesses of Mg materials.…”
mentioning
confidence: 99%
“…However, the main drawbacks of conventional Mg alloys are insufficient mechanical strength and rapid corrosion accompanied with hydrogen gas evolution, pH increase, and premature loss of mechanical integrity 5 . Previous studies on surface treatment 6 and element alloying 7 of Mg for stent application showed that these two methods enhanced the performance of Mg and its alloys at some degree but not sufficiently. More sophisticated efforts are in need to fully overcome such weaknesses of Mg materials.…”
mentioning
confidence: 99%
“…(b)]. It has been reported that the dextran layer serves as both a matrix and a reservoir . Even though dextran is water‐soluble, it might initially affect the surrounding cells such as endothelial cells, and it may affect various biological cascades.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the dextran layer serves as both a matrix and a reservoir. 36 Even though dextran is water-soluble, it might initially affect the surrounding cells such as endothelial cells, and it may affect various biological cascades. Another study explored the effects of dextran on endothelial progenitor cells, and found that dextran could increase the expression of endothelial marker genes and endothelial cell-related transcription factor genes.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that such a three-layer hybrid coating was useful to improve the vascular biocompatibility of Mg stent materials. In their study, biodegradable and nontoxic polymers, dextran, and polyglutamic acid (PGA) were used to fabricate protective coatings on Mg alloy AZ31 [45]. For the three-layer design, the first and third dextran layers served as the matrix and reservoir, and the middle PGA layer was used as the rate-controlling material.…”
Section: Antibacterial-functionalized Magnesium Alloys Used As Cardiomentioning
confidence: 99%